Pelaksanaan Pemotongan Sapi Di Rumah Potong Hewan Giwangan - ARIYANTO, Abi ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Provision of adequate foster meat in the region of Yogyakarta city became one of the tasks the Department of Industry, Trade Cooperatives and Agriculture (Disperindagkoptan). The purpose of this final preparation is knowing infrastructure Slaughterhouse, cutting process, and the cows which are not recorded in RPH Giwangan, Yogyakarta. Retrieval and collection of data was done by recording the letter levy, direct observation of cattle slaughtering activities. During the Job Training is seen that RPH infrastructure is complete, the process of slaughtering were in accordance with existing procedures, and no cows weren’t recorded in Slaughterhouse Giwangan.